À tire-d’aile. Les portraits d’oiseaux de John James Audubon (1785-1851) : l’art naturaliste envers ou contre le vivant ? - Marion Bélouard (Interfaces)
This article explores the complex relationship between artistic creation, scientific conservation, and the destruction of the natural world in the work of John James Audubon. The author examines the status of Birds of America as an archive of the living world in the history of naturalist art, from an ecocritical perspective. She analyses the extent to which this ornithological collection, while aiming to increase the knowledge of species, is inextricably linked to predatory practices against avifauna. Beyond the theoretical and original value of the illustrations, the way Audubon stages bird specimens in elaborate artistic compositions shapes our perception of the living world and contributes to the cultural construction of the idea of “nature”. By situating Audubon’s work within the colonial context and the history of the formation of nation-states, this study offers a nuanced reassessment of his legacy in the light of contemporary environmental issues.